The Gender Dimension of the Inclusion: The Case of the Western Siberian Universities - Efimova G.Z; Volosnikova L.M; Ogorodnova O.V (Moscow State University of Psychology and Education, 2018)
The paper focuses on the attitude of university staff towards students with disabilities and on the readiness for inclusive higher education in members of the academic staff. It is stressed that one of the main tasks of the resource and training centers network is to help overcome such powerful barriers as social stereotypes and incompetence in inclusive education and to assist university teachers in establishing contacts and interaction with students with disabilities. The paper presents a study that involved 2181 university teachers from 10 universities of the Tyumen region. The study had two objectives: first, to explore the attitude of the academic staff of the universities to students with disabilities and the former's readiness for inclusive education; secondly, to reveal gender differences in relation to inclusion. The main outcomes of the study are as follows. Women working in higher education are more positive towards inclusive education and its prospects, more tolerant and sympathetic to persons with disabilities. They are more focused on active inclusive behavior, on acquiring new knowledge and skills, and on rendering extensive support to students with disabilities. They value their own skills and competencies in inclusive teaching and collaboration highly enough. The paper concludes that women working at the universities of the Tyumen regions are an important resource for achieving the goals of resource training centers in the field of inclusive higher education.